Experimental investigation on physical properties of banana/E-glass fiber reinforced hybrid interpenetrating polymer network composites. (2021) - Bharani Kumar, S.; Sekar, S.D.; Mothilal, T.; Sivakkumar, G.; Lavanya, R.; Meenakshi, C.M.; Manivannan, S.
Abstract: Researchers are often trying to find out the various renewable energy sources to continuously feed the growing energy demands Now a day's researchers are much interested to carry out their investigation in the area of finding out the various eco friendly materials in order to completely or partially eliminate the usage of conventional of type of materials, as well as to avoid the environmental pollution. In this particular study, the six combinations (E-Glass/Banana fiber reinforcement) of interpenetrating polymer network laminate have been fabricated and their physical strengths were examined with help of the tensile, flexural, impact and moisture absorption test as per the ASTM standards. The results showed that, the neat E-Glass fiber reinforced IPN laminate exhibited the tensile physical strength value as 212.42 MPa, flexural strength of 3.2 kN, impact strength value of 4.62 J and finally water uptake percentage was 1.8%. Whereas the IPN laminate comprises of banana fiber and E-glass fiber hybridization has shown the (60 wt of E-Glass/40 wt of banana) tensile strength value as 179.53 MPa, flexural strength value of 2.12 kN, impact strength value of 4.12 J and moisture absorption percentage was 8.53%. All the test results were compared with each other and significant contribution of the hybridisation is presented in this study.